2015
DOI: 10.1161/strokeaha.115.009324
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds Predict Intracerebral Hemorrhage in Hemodialysis Patients

Abstract: Background and Purpose-In hemodialysis patients, previous reports have described a high prevalence of cerebral microbleeds (CMBs), but no longitudinal studies have been performed to determine the clinical significance of CMBs in these patients. In this study, we investigated whether the presence of CMBs was a predictor of future strokes in hemodialysis patients. Methods-Cranial MRI, including T2*-weighted magnetic resonance imaging, was performed on 179 hemodialysis patients with no past history of cerebrovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Hemodialysis patients were reported to have a high prevalence of cerebral microbleeds (CMBs) [35,36], and older age and high blood pressure (BP) were found to be powerful factors associated with the presence of CMBs [35]. Actually, the presence of CMBs is a powerful and significant predictor of intracerebral hemorrhage, with a hazard ratio of 26.5 (95% CI 2.8-244.9) [37]. Figure 6 shows declining RRs of mortalities in all age groups over a recent 20-year period.…”
Section: Malignant Tumormentioning
confidence: 99%
“…Hemodialysis patients were reported to have a high prevalence of cerebral microbleeds (CMBs) [35,36], and older age and high blood pressure (BP) were found to be powerful factors associated with the presence of CMBs [35]. Actually, the presence of CMBs is a powerful and significant predictor of intracerebral hemorrhage, with a hazard ratio of 26.5 (95% CI 2.8-244.9) [37]. Figure 6 shows declining RRs of mortalities in all age groups over a recent 20-year period.…”
Section: Malignant Tumormentioning
confidence: 99%
“…Diminished eGFR appears to be an independent risk factor for cerebral microbleeds, raising the possibility that a uremic milieu may predispose to microbleed formation [115]. In a cohort of Japanese hemodialysis patients who were strokefree at baseline, presence of cerebral microbleeds was an independent predictor of intracerebral hemorrhage during a 5-year follow-up period [116].…”
Section: Cerebral Microbleedsmentioning
confidence: 99%
“…Cerebral microbleeds have been reported to affect the occurrence of cerebral hemorrhage [26][27][28][29]. Naganuma et al [29] performed cranial MRI, including T2*-weighted MRI, on 179 hemodialysis patients with no past history of cerebrovascular events and followed them prospectively until death or renal transplantation.…”
Section: Prevalence Of Cerebral Microbleeds and Risk Of Brain Hemorrhagementioning
confidence: 99%
“…Naganuma et al [29] performed cranial MRI, including T2*-weighted MRI, on 179 hemodialysis patients with no past history of cerebrovascular events and followed them prospectively until death or renal transplantation. They showed that intracerebral hemorrhage occurred in only one of 134 (0.7 %) patients without cerebral microbleeds, whereas it occurred in 11 of 45 (24.4 %) patients with cerebral microbleeds during a median follow-up period of 5.0 years.…”
Section: Prevalence Of Cerebral Microbleeds and Risk Of Brain Hemorrhagementioning
confidence: 99%